2007
DOI: 10.1093/hmg/ddm112
|View full text |Cite
|
Sign up to set email alerts
|

Common genetic variants and haplotypes in renal CLCNKA gene are associated to salt-sensitive hypertension

Abstract: Abnormal renal reabsorption of sodium (Na(+)) is likely to play a role in the pathogenesis of salt-sensitivity. In the kidney, chloride channels CLC-Ka (gene CLCNKA) and CLC-Kb (gene CLCNKB) and their subunit Barttin (gene BSND) have important effects on the control of Na(+) and water homeostasis. We investigated if single nucleotide polymorphisms (SNPs) or haplotypes within CLCNKA, CLCNKB and BSND loci affect salt-sensitivity in hypertensive subjects. Associations between blood pressure (BP) change after Na(+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 47 publications
1
45
0
3
Order By: Relevance
“…In addition, it has been recently shown that salt-sensitive hypertension may be associated with chloride channel polymorphism (2). Therefore, our observation of a significant increase in active channel density, but not of other channel biophysical characteristics, in DCT cells of MHS rats is well in agreement with the possibility of an increased transepithelial NaCl flux during the maintenance phase of hypertension.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, it has been recently shown that salt-sensitive hypertension may be associated with chloride channel polymorphism (2). Therefore, our observation of a significant increase in active channel density, but not of other channel biophysical characteristics, in DCT cells of MHS rats is well in agreement with the possibility of an increased transepithelial NaCl flux during the maintenance phase of hypertension.…”
Section: Discussionsupporting
confidence: 90%
“…CLCNKA mutations were associated with high blood pressure (10) or heart failure (11). In contrast, loss-of-function of hClC-Kb results in Bartter syn-drome type III, a genetic human disease condition characterized by hypokalemia, metabolic alkalosis, polyuria, polydipsia, and low blood pressure at increased levels of renin and aldosterone (9,12,13).…”
Section: Affected Kidneys and The Clinical Symptoms Of Bartter Syndromentioning
confidence: 99%
“…[69][70][71] As mentioned, furosemide may exert some of its affect through an inhibitory action on ClC-K channels, and recently a number of novel compounds with direct ClCKa/b inhibition have been proposed as a future class of antihypertensive agents, following demonstration that they provoke a diuresis in rats. 72 …”
mentioning
confidence: 99%